NOTICIAS SOBRE ARQUITECTOS, MAESTROS ALARIFES, CANTEROS Y CARPINTEROS DE MURCIA (1700-1725) - Cabello Velasco, Rafaela (Imafronte, 1995)
Record Archives and the notarial files contained there in are an important source of information for research connected with the History of Art. Notarial records usually document, in the form of contracts or binding agreements, the undertaking of more or less relevant works. It is even possible to find valuable information on wills, inventories or letters of attorney. An examination of all the notarial documents drawn up in Murcia in the first quarter of the 18th century has made it possible to produce a long list of architects, master-builders, stonemasons and carpenters, with different information regarding their activities. This is the basis of the study, the principal aim of which is to offer a list of information on these artists which will undoubtedly be useful for any research into the subject.